Impact of electron beam and ethyl methane sulphonate on chlorophyll mutations in rice genotypes ASD 16 and Norungan - Prasannakumari, M.; Gnanamalar, R. P.; Vanniarajan, C.; Souframanien, J.; Anand, G.; Renuka, R.; Singh, R. Durai (Journal of Phytology, 2024)
Induced mutagenesis facilitates the creation of novel gene combinations within a plant genome, preserving its basic structure. This study investigates the impact of electron beam radiation and ethyl methane sulphonate (EMS) on chlorophyll mutations in rice genotypes, ASD 16 and Norungan. The seeds were irradiated with five different doses of electron beam and EMS during rabi 2021-22. The M1 generation was assessed for seedling survival, seedling height and spikelet fertility followed by an identification of chlorophyll mutants in the M2 generation. At specific mutagen doses, ASD 16 and Norungan exhibited the genotypic difference for chlorophyll mutants. Various chlorophyll mutations, such as albino, chlorina, xantha, striata, viridis, albomaculata, alboviridis and xanthoviridis were observed. ASD 16 was more sensitive to both mutagens, while Norungan showed a broader response. EMS proved to be a more effective in inducing mutations than the electron beam. Lower and moderate mutagen doses demonstrated higher efficiency indicating the importance of optimizing mutagenic conditions. This study illuminates the significance of chlorophyll mutants genetic makeup varietal differences. The strong and diverse response observed in Norungan underscores its suitability for mutation breeding programmes. These findings contribute to the efficient utilisation of mutagenesis in improving rice traits providing practical implications for elevating crop quality and promoting genetic diversity in rice cultivation.